1996
DOI: 10.1029/96gl01856
|View full text |Cite
|
Sign up to set email alerts
|

Unexpectedly low ozone concentration in midlatitude tropospheric ice clouds: A case study

Abstract: Raman lidar measurements of ozone, water vapor, and cirrus optical properties over northern Germany (53.4°N, 10.4deg;E) in autumn 1995 are presented. In contrast to smooth ozone profiles with values of 50 to 100 ppbv in a cloud‐free and dry upper troposphere, pronounced minima in the ozone distribution with values close to zero were found several times in the presence of ice cloud layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…This depletion occurs at the lower limit of the SAGE sensitivity, and the reality of SAGE data at low latitudes has been questioned on the grounds that large depletion is not expected there. But there is evidence that cirrus clouds, which are abundant at the altitudes and latitudes in question, may activate ozone depletion (Borrmann et al 1996 ;Reichardt et al 1996). At any rate, as a sensitivity study, for the want of better measurements, we take the SAGE data at face value.…”
Section: Recent Years: 1979-1995mentioning
confidence: 99%
“…This depletion occurs at the lower limit of the SAGE sensitivity, and the reality of SAGE data at low latitudes has been questioned on the grounds that large depletion is not expected there. But there is evidence that cirrus clouds, which are abundant at the altitudes and latitudes in question, may activate ozone depletion (Borrmann et al 1996 ;Reichardt et al 1996). At any rate, as a sensitivity study, for the want of better measurements, we take the SAGE data at face value.…”
Section: Recent Years: 1979-1995mentioning
confidence: 99%
“…Heterogeneous reactions on or inside of these droplets or cloud particles could convert the inactive reservoir species C1ONO2, HC1, and HOC1 into reactive forms of chlorine (Solomon et al [1986]), which ultimately may influence ozone. Cases of "unusually low ozone in cirrus clouds" have recently been reported by Reichardt et al [1996], and the potential of cirrus clouds for heterogeneous chlorine activation has been addressed by Borrmann et al [1996]. Depending on the phase and chemical composition of the aerosol particles and on the abundances of water vapor and the reservoir species, the reaction efficiencies can vary over wide ranges (Hanson et The C10 …”
Section: Introductionmentioning
confidence: 99%
“…Borrmann et al (1996) showed that cirrus clouds might lead to heterogeneous Chemical reactions similar to those taking place on Polar Stratospheric Clouds and suggested that these clouds could affect the abundances of ozone. Some observational studies (Reichard et al, 1996;Roumeau et al, 2000) have found such diminutions of ozone in the presence of cirrus at both mid-latitude and tropical sites. While several studies (Stowe et al, 1989;Wylie et al, 1994;Wang et al, 1996) reported frequent cirrus clouds near the tropopause, Solomon et al (1997) suggested that the chemistry associated to these clouds at mid-latitudes may contribute ozone depletion observed at mid-latitudes in the lower stratosphere and would permit to reconcile observed and modeled ozone trends at mid-latitudes (Meilinger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%